The Effect of Marginal Tax Rates on Taxable Income: A Panel Study of the 1986 Tax Reform Act - Feldstein, Martin (Journal of Political Economy, 1995)
This paper uses a Treasury Department panel of more than 4,000 taxpayers to estimate the sensitivity of taxable income to changes in tax rates based on a comparison of the tax returns of the same individual taxpayers before and after the 1986 tax reform. The analysis emphasizes that the response of taxable income involves much more than a change in the traditional measures of labor supply. The evidence shows an elasticity of taxable income with respect to the marginal net-of-tax rate that is at least one and that could be substantially higher. The implications for recent tax rate changes are discussed. Copyright 1995 by University of Chicago Press.